Covariation of Pluripotency Markers and Biomechanical Properties in Mouse Embryonic Stem Cells - Brookes, Oliver; Thorpe, Stephen D.; Rigby Evans, Olga; Keeling, Michael C.; Lee, David A. (Frontiers in Cell and Developmental Biology, 2022)
Pluripotent cells are subject to much interest as a source of differentiated cellular material for research models, regenerative medical therapies and novel applications such as lab-cultured meat. Greater understanding of the pluripotent state and control over its differentiation is therefore desirable. The role of biomechanical properties in directing cell fate and cell behavior has been increasingly well described in recent years. However, many of the mechanisms which control cell morphology and mechanical properties in somatic cells are absent from pluripotent cells. We leveraged naturally occurring variation in biomechanical properties and expression of pluripotency genes in murine ESCs to investigate the relationship between these parameters during the pluripotent state. We observed considerable variation in a Rex1-GFP expression reporter line and found that this variation showed no apparent correlation to cell spreading morphology, either on a parameter-by-parameter basis, or when evaluated using a combined metric derived by PCA from the four individual criteria. We further confirmed that cell volume does not co-vary with Rex1-GFP expression. Interestingly, we did find that a subpopulation of cells that were readily detached by gentle agitation collectively exhibited higher expression of rex1 and nanog, and reduced lmnA expression, suggesting that elevated pluripotency gene expression may correlate with reduced adhesion to the substrate. Furthermore, AFM/fluorescent quantitative imaging revealed a connection between compliance and Rex1-GFP reporter expression, in that the cells expressing the most Rex1 (having greater than median Rex1-GFP integrated density) have a range which includes higher compliance values distinct from those seen in cells expressing less Rex1 (Rex1-GFP integrated density below median). These observations indicate some interaction between pluripotency gene expression and biomechanical properties, but also support a strong role for other interactions, independent of the core transcriptional network that supports pluripotency.